General Problems of Professional Orientation of Young People with Severe Mental Development Disorders and Intellectual Disabilities - N.A. Karpova (Moscow State University of Psychology and Education, 2020)
In Russian society, more preciseattention is paid to the problems of vocational guidance, training, employment of young people with severe mental disabilities. This article reveals the problems of professional orientation of young people with severe mental development disorders. The specialists of the Center for Social Adaptation and Professional Training of Young People with Autism Spectrum Disorders with Mental Disabilities at Technological College No. 21 in Moscow for a long time deal with professional orientation and education of people with severe mental disorders. The Center for Social Adaptation and Professional Training for Young People with Autism Spectrum Disorders with Pronounced Mental Disabilities Technological College No. 21 in Moscow is working on vocational guidance and training. The work demonstrates the importance of the process of vocational guidance for people with severe developmental disorders, Also article reveals certain difficulties in solving this problem. Two large groups of problems are distinguished - external and internal: social problems that impede the ability of young people with severe mental disabilities to choose a profession, and problems associated with the organization of career guidance activities themselves. It is noted that new opportunities for career guidance are currently opening up, as specialists shift the focus from the limitations of young people to their advantages and opportunities.